The Effect Of Reference Group And Perceived Price On Brand Switching E-Commerce Shopee In Medan - Purba, Natria R. A.; Safrin, Feby Aulia (Paspama Institute, 2023)
Every e-commerce in Indonesia creates innovations and shopping promotions that can attract consumers to use their platform. They also offer a lot of similar goods which makes consumers more selective in choosing the goods they want to buy and are vulnerable to brand switching behavior in product purchases. This study aims to determine how the influence of reference groups and price perceptions on brand switching to Shopee e-commerce in Medan, either partially or simultaneously. The type of research is quantitative research with an associative approach. The sampling technique is purposive sampling which collects 100 respondents. The data analysis technique used is validity test, reliability test, classical assumption test, multiple linear regression test, T test, F test and coefficient of determination test. The results showed that the reference group and the perceived price had a positive and significant effect on Shopee's e-commerce brand switching partially and simultaneously. The correlation coefficient value is 0.657 which shows a direct correlation between reference group, perceived price to brand switching. The value of R Square is 0.432, meaning that reference group and perceived price simultaneously have an effect of 43.2% on brand switching, while the effect on other variables was not examined in this study.